Economic Analysis of Projects in a Greenhouse World - Hamilton, Kirk; Stover, Jana (World Bank, Washington, DC, 2012)
Recent carbon market prices are substantially lower than mean or median estimates of the social cost of carbon in the literature. Intuition would therefore suggest that 'investment errors' are being made, in the sense that markets favor higher carbon-emitting projects, while global welfare would be larger with lower carbon-emitting projects. This intuition is correct in specific circumstances, but not others. For any comparison of two alternative projects, there is a carbon switching price that equalizes their net social benefits. From the perspective of maximizing global welfare, investment errors only occur when this switching price lies between the carbon market price and the social cost of carbon. Data on the costs of high-carbon and low-carbon electric generation projects suggest that there is no financing gap using mean or median published figures, but for precautionary (95th percentile) choices of the social cost of carbon, there is a financing gap between carbon market prices and the switching price that would trigger investment in the global welfare-maximizing low-carbon project. A global carbon fund to finance this gap could be conceived, but stricter emission caps and reforms of carbon markets are likely to be a more efficient solution to the problem.